2016
DOI: 10.1038/srep38204
|View full text |Cite
|
Sign up to set email alerts
|

The Hha-TomB Toxin-Antitoxin System Shows Conditional Toxicity and Promotes Persister Cell Formation by Inhibiting Apoptosis-Like Death in S. Typhimurium

Abstract: Toxin-antitoxin (TA) modules are two component “addictive” genetic elements found on either plasmid or bacterial chromosome, sometimes on both. TA systems perform a wide range of functions like biofilm formation, persistence, programmed cell death, phage abortive infection etc. Salmonella has been reported to contain several such TA systems. However, the hemolysin expression modulating protein (Hha) and its adjacent uncharacterized hypothetical protein TomB (previously known as YbaJ), have not been listed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Many factors are involved in the pathogenesis of bacteria specially S. typhi [9]. One of these factors is toxin-antitoxin (TA) system which has been considered today [7]. Since the TA system plays an essential role in the pathogenesis of bacteria [10], we decided to analyze the potent TA loci by bioinformatics method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors are involved in the pathogenesis of bacteria specially S. typhi [9]. One of these factors is toxin-antitoxin (TA) system which has been considered today [7]. Since the TA system plays an essential role in the pathogenesis of bacteria [10], we decided to analyze the potent TA loci by bioinformatics method.…”
Section: Resultsmentioning
confidence: 99%
“…Control and treatment of S. typhi infection has become a challenge [6]. On the other side, according to the most recent studies, TA system is significant as a potent antimicrobial target and plays an important role as a basic principle in the pathogenesis of bacteria [7].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of bacterial persistence (persister bistability) – a non-inherited antibiotic tolerance in a minute fraction of the cellular population 1 11 is a proven example of the existence of phenotypic multiplicity in a genetically homogeneous population of bacterial cells 12 . This phenomenon was discovered in 1944 13 and its essence lies in the fact that an antibiotic-sensitive population of bacterial cells practically always, even after prolonged antibiotic therapy, contains a very small number of cells (10 −3 –10 −6 ) possessing tolerance to the antibiotic and therefore is capable of restoring cellular population after withdrawal of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the functional activity of persister cells revealed a significantly higher expression of genes belonging to the stress response systems, including the toxin-antitoxin (TA) systems 8 , 11 , 15 , 16 . The study of mutant genes belonging to various TA systems confirmed their participation in the formation of persister cells 12 , 22 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, bioinformatics analysis suggested about 11-19 type II TA modules in Salmonella Typhimurium of which, the phd/doc and TacAT systems(Cheverton et al, 2016) induce multidrug-resistant persisters in this pathogen after being activated by nutrient-deprived environment in vacuoles. Similarly, a study byJaiswal et al (2016) suggested that Hha (toxin) and TomB (antitoxin), belonging to the bonafide type II TA system, crucially play role in persister cell formation by inhibiting apoptosis like cell death of Salmonella Typhimurium.TA also plays a significant role in mediating persistence of oraldwelling bacteria such as S. mutans and Aggregatibacter actinomycetemcomitans. S. mutans, present inside the biofilm in oral cavity,…”
mentioning
confidence: 98%